2021
DOI: 10.1126/science.abc9141
|View full text |Cite
|
Sign up to set email alerts
|

Chronoculture, harnessing the circadian clock to improve crop yield and sustainability

Abstract: Human health is dependent on a plentiful and nutritious supply of food, primarily derived from crop plants. Rhythmic supply of light as a result of the day and night cycle led to the evolution of circadian clocks that modulate most plant physiology, photosynthesis, metabolism, and development. To regulate crop traits and adaptation, breeders have indirectly selected for variation at circadian genes. The pervasive impact of the circadian system on crops suggests that future food production might be improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 77 publications
2
90
0
Order By: Relevance
“…Moreover, MQ had additional genes under positive selection in the photomorphogenesis, flowering and circadian pathway: LIGHT-DEPENDENT SHORT HYPOCOTYLS ( LSH ), ENHANCER OF AG-4 ( HUA2 ) and LHY . In addition to being under positive selection, LHY is also tandemly duplicated in Vmac (Figure 3B), suggesting it may play an important role in the domestication of cranberry consistent with the selection pressure on core circadian genes in other crops [39].…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, MQ had additional genes under positive selection in the photomorphogenesis, flowering and circadian pathway: LIGHT-DEPENDENT SHORT HYPOCOTYLS ( LSH ), ENHANCER OF AG-4 ( HUA2 ) and LHY . In addition to being under positive selection, LHY is also tandemly duplicated in Vmac (Figure 3B), suggesting it may play an important role in the domestication of cranberry consistent with the selection pressure on core circadian genes in other crops [39].…”
Section: Resultsmentioning
confidence: 88%
“…For the purpose of exploring the relationship between CCA1-PRR9 and RVE4-PRR7 , a simplified model of their interactions was developed (Figure 1A) (Shalit-Kaneh et al, 2018); more detailed models can be found in recent reviews (McClung, 2021; Steed et al, 2021). In general, PRR7/9 are negatively and positively regulated by CCA1/LHY and RVE4/RVE8 respectively, while in turn PRR7/9 negatively regulate both.…”
Section: Resultsmentioning
confidence: 99%
“…The plant circadian clock ensures biological processes occur at the proper time-of-day (TOD) regardless of predictable as well as random environmental changes, which is why it has been a target for plant domestication (Bendix et al, 2015; Creux and Harmer, 2019; McClung, 2021; Steed et al, 2021). The molecular mechanisms of the plant circadian clock were initially worked out in the model plant Arabidopsis thaliana and now there is a growing body of work across an array of crop and ornamental plants (Sanchez and Kay, 2016; McClung, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of the circadian clock system in crops are diverse and conservative, but the mechanism of the circadian clock components in regulating the growth and development of crops still needs further study. The general impact of the circadian clock system on crops suggests that, by modifying the circadian rhythm, designing the timing of transgene expression and applying agricultural treatments at the most effective time of the day, future food production may be improved ( Steed et al, 2021 ). Analyzing how the circadian clock system regulates the growth and development process of crops will hopefully illuminate the theoretical basis of chronobiology, provide high-quality genetic resources for crop molecular breeding, and increase crop yields ( Wei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, more and more reports suggested that Ppd-1 is a member of the circadian clock. Steed et al (2021) indicated that on the basis of its relationship to Arabidopsis , PRR37 is assumed to have potential roles in the oscillator. Cao et al (2021) described the PRRs, including the wheat Ppd-1 gene, as a major component of the circadian clock.…”
Section: Discussionmentioning
confidence: 99%